Food insecurity status and its contributing factors in slums' dwellers of southwest Iran, 2021: a cross-sectional study - Hassan Joulaei; Parisa Keshani; Zohre Foroozanfar; Sima Afrashteh; Zahra Hosseinkhani; Mohammad Ali Mohsenpour; Ghasem Moghimi; Arash Homayouni Meymandi (BMC, 2023)
Abstract Background One major factor causing food insecurity is believed to be poverty. Approximately 20 million Iranians live in slums with a vulnerable socioeconomic context. The outbreak of COVID-19, on top of the economic sanctions against Iran, has increased this vulnerability and made its inhabitants prone to food insecurity. The current study investigates food insecurity and its associated socioeconomic factors among slum residents of Shiraz, southwest Iran. Methods Random cluster sampling was used to select the participants in this cross-sectional study. The heads of the households completed the validated Household Food Insecurity Access Scale questionnaire to assess food insecurity. Univariate analysis was utilized to calculate the unadjusted associations between the study variables. Moreover, a multiple logistic regression model was employed to determine the adjusted association of each independent variable with the food insecurity risk. Results Among the 1227 households, the prevalence of food insecurity was 87.20%, with 53.87% experiencing moderate and 33.33% experiencing severe food insecurity. A significant relationship was observed between socioeconomic status and food insecurity, indicating that people with low socioeconomic status are more prone to food insecurity (P < 0.001). Conclusions The current study revealed that food insecurity is highly prevalent in slum areas of southwest Iran. The socioeconomic status of households was the most important determinant of food insecurity among them. Noticeably, the coincidence of the COVID-19 pandemic with the economic crisis in Iran has amplified the poverty and food insecurity cycle. Hence, the government should consider equity-based interventions to reduce poverty and its related outcomes on food security. Furthermore, NGOs, charities, and governmental organizations should focus on local community-oriented programs to make basic food baskets available for the most vulnerable households.